The cresst dark matter search - Bawkina, I; Bento, A; Hauff, D; Huff, P; Lang, R; Majorovits, B; Pantic, E; Petricca, F; Prbst, F; Seidel, W; Stodolsky, L; Henry, S; et al. (2007)
CRESST I1 is a WIMP search experiment using cryogenic detectors to detect heat and scintillation signals in Caw04 crystals simultaneously. Competitive limits on the coherent WIMP-nucleon scattering cross section and other results from runs from the upgrade to CRESST I1 are shown. New features and upgrades installed on the CRESST I1 setup are described and the status of the experiment is presented.